Consumer Legal Protection On The Implementation Of E-Commerce Using Instagram With A Pre-Order System During The Covid-19 Pandemic - Ainul Millah Al-Mumtaza AL-MUMTAZA; Muhammad RUSTAMAJI (International Journal of Environmental, Sustainability, and Social Science, 2022)
The implementation of e-commerce in Indonesia is growing rapidly and has its own online sales place, which is commonly called a marketplace. However, the current rapid technological developments that are used to promote not only use the marketplace but can also be done on social media. The social media that is widely used is Instagram which in carrying out sales transactions uses a pre-order system. The covid-19 virus is endemic. The Korean Hallyu virus is also endemic with the number of merchandise per Kpop sold with a pre-order system. This situation is widely used by people who want to start a business by making it a job during the current pandemic by selling various merchandise and albums for Korean idol groups. But not a few of the sellers' abuse this situation to take advantage of themselves to the detriment of others. Many take advantage of the comebacks of each idol group by opening pre-orders for the album and merchandise sales where buyers are required to pay an advance to the seller, but after the goods are finished being produced, the account does not continue the transaction to the buyer, so the goods do not reach the buyer. This action is very detrimental to many buyers who participate in e-commerce transactions on Instagram using the pre-order system, so buyers must get legal protection rights.